DESIGN OF FIXED-TYPE OFFSHORE PLATFORM STRUCTURES UNDER IN-SERVICE CONDITIONS AND ANALYSIS OF THE REVERSE UPENDING METHOD IN THE RIG-TO-REEF DECOMMISSIONING PROCESS - Abdillah Al Khoir, Mufida
Crude oil and natural gas are essential natural resources for many industries, making their supply crucial. SKK Migas has targeted increasing oil and gas production to one million barrels per day by 2030. Offshore platforms are vital components in the exploration and production of these resources. Planning and constructing offshore platforms require analysis of load, inplace conditions, seismic activity, and fatigue. Additionally, the service life of the structure and the availability of oil and gas wells must be considered. According to Government Regulation of the Republic of Indonesia No. 17 of 1974 on the supervision of oil and gas exploitation in offshore areas, Article 21 states that structures no longer in use must undergo decommissioning. Decommissioning can be executed through complete removal or partial removal using various methods such as rig to reef, toppling, or floater, depending on the structure's characteristics and location.One method that can be utilized in the rig to reef process is reverse upending, in which the structure’s orientation is changed from vertical to horizontal after being lifted using a main hook attached to one side of the structure and an auxiliary hook connected to the top. The structure is then lowered to the seabed. Structural analysis during the reverse upending process includes considerations of mudline clearance, stability at yaw angles, and the maximum loads encountered by each hook, along with the slings connected to them. Lifting analysis is also performed prior to the reverse upending process or when the structure is lifted vertically. The application of a Dynamic Amplification Factor (DAF) to the maximum static loads during lifting is necessary to consider potential dynamic forces. This reverse upending process must also follow the criteria outlined in GL Noble Denton guidelines 0027 and 0028.